Seasonal changes of perineuronal nets and song learning in adult canaries (Serinus canaria) - Cornez, Gilles (Behav Brain Res, 2019)
Songbirds learn their song during a sensitive period of development associated with enhanced neural plasticity. In addition, in open-ended learners such as canaries, a sensitive period for sensorimotor vocal learning reopens each year in the fall and leads to song modifications between successive breeding seasons. The variability observed in song production across seasons in adult canaries correlates with seasonal fluctuations of testosterone concentrations and with morphological changes in nuclei of the song control system (SCS). The sensitive periods for song learning during ontogeny and then again in adulthood could be controlled by the development of perineuronal nets (PNN) around parvalbumin-expressing interneurones (PV) which limits learning-induced neuroplasticity. However, this relationship has never been investigated in the context of adult vocal learning in adult songbirds. Here we explored PNN and PV expression in the SCS of adult male Fife Fancy canaries in relation to the seasonal variations of their singing behaviour. We found a clear pattern of seasonal variation in testosterone concentrations and song production. Furthermore, PNN expression was significantly higher in two specific song control nuclei, the robust nucleus of the arcopallium (RA) and the Area X of the basal ganglia, during the breeding season and during the later stages of sensorimotor song development compared to birds in an earlier stage of sensorimotor development during the fall. These data provide the first evidence that changes in PNN expression could represent a mechanism regulating the closing-reopening of sensitive periods for vocal learning across seasons in adult songbirds.